2012
DOI: 10.1007/978-3-642-27994-2_12
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-Labeled Bombesin Analogs for Receptor-Mediated Imaging

Abstract: Targeted receptor-mediated imaging techniques have become crucial tools in present targeted diagnosis and radiotherapy as they provide accurate and specific diagnosis of disease information. Peptide-based pharmaceuticals are gaining popularity, and there has been vast interest in developing (68)Ga-labeled bombesin (Bn) analogs. The gastrin-releasing peptide (GRP) family and its Bn analog have been implicated in the biology of several human cancers. The three bombesin receptors GRP, NMB, and BRS-3 receptor are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 185 publications
0
13
0
1
Order By: Relevance
“…A recent prospective, double-blind study(NETTER-1) reported in preliminary form[51], in 230 patients (randomized 1:1) with advanced, inoperable, progressive, small intestinal, metastatic ileal carcinoid tumors, demonstrates for the first time, that using a 177 Lutetium-labeled-somatostatin-analogue, results in a highly significant extension of progressive-free survival compared to patients not treated with the 177 Lutetium-labeled-somatostatin analogue(p<0.0001) and likely extension of survival(23 vs 67 deaths), with acceptable toxicity. Unfortunately, most common neoplasms do not overexpress somatostatin-receptors, however, many overexpress BnR’s[1,23], which has led to markedly increased interest in using a similar approach using Bn-analogues to both image primary tumor location and extent of these tumors,as well as to target them with cytotoxic-agents[12,13,16•,52]. …”
Section: Imaging and Targeted-delivery Of Cytotoxic-agents To Neopmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent prospective, double-blind study(NETTER-1) reported in preliminary form[51], in 230 patients (randomized 1:1) with advanced, inoperable, progressive, small intestinal, metastatic ileal carcinoid tumors, demonstrates for the first time, that using a 177 Lutetium-labeled-somatostatin-analogue, results in a highly significant extension of progressive-free survival compared to patients not treated with the 177 Lutetium-labeled-somatostatin analogue(p<0.0001) and likely extension of survival(23 vs 67 deaths), with acceptable toxicity. Unfortunately, most common neoplasms do not overexpress somatostatin-receptors, however, many overexpress BnR’s[1,23], which has led to markedly increased interest in using a similar approach using Bn-analogues to both image primary tumor location and extent of these tumors,as well as to target them with cytotoxic-agents[12,13,16•,52]. …”
Section: Imaging and Targeted-delivery Of Cytotoxic-agents To Neopmentioning
confidence: 99%
“…These include reviews of general advances in all these aspects[2••,3]; the role of BRS-3 in obesity and diabetes[5]; the role of BnR’s in feeding disorders[2••,8]; pruritis[2••,9]; CNS function/disorders including memory, stress[2••,10]; lung diseases[2••]; inflammatory disorders[2••,11]; the signaling especially in cancer[2••,7] and the development of BnR-ligands as possible imaging modalities[2••,12,13]. In the present paper the possible role of BnRs in neoplastic processes will be concentrated on with a view to the use of their overexpression/growth effects by many human-cancers as a potential novel target for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…163e165 Radiolabelled somatostatin analogues that have been used with SPECT include 99m Tc, 123 I, and 111 In, and with PET include 68 Ga and 64 Cu. SSTR-directed radionuclide therapies have shown 80% disease stabilisation rates with better response rates from newer 90 Yand 177 Lu-labelled SSTR therapies 163e165 (Fig 10).…”
Section: Mfi Of Receptorsmentioning
confidence: 97%
“…174,175 PET tracers, such as 64 Cu-DOTA-[Lys3]-BN and 68 Ga-labelled-BN, have been tested for safety and efficacy in prostate and pancreatic cancer xenografts models. 176,177 The HER-2/neu receptor is a member of the EGF family and is amplified in many cancers and is both a prognostic as well as a therapeutic marker. 178,179 Recently developed, novel two-component gadolinium-based MRI contrast agents, i.e., avidin-Gd conjugated with DTPA for HER-2/neu receptor imaging and anti-HER-2/neu antibody herceptin labelled with the 68 Ga for PET imaging in breast cancer xenografts have been used to study the degradation of HER-2/neu in response to a novel anti-cancer drug Hsp90-inhibitor 17-allylaminogeldanamycin (17-AAG).…”
Section: Mfi Of Receptorsmentioning
confidence: 99%
“…Jeho širšímu rozšíření zatím brá-nila suboptimální dostupnost spojená s výše zmíněnými problémy. Označitel-ných a využitelných markerů je nicméně velké množství, v současné době prová-děné studie s PSMA (prostate-specifi c membrane antigen) [68][69][70] či bombesinem [71] (tumorový marker např. pro malobuněčný karcinom plic, neuroblastomy či nádory žaludku) označenými gal liem jsou pouhými prvními příklady dynamicky se rozvíjejícího nového pole vysoce specifi ckých PET radiofarmak.…”
Section: Závěrunclassified